Properties of crumb rubber concrete paving blocks with SBR latex - Ling, Tung Chai; Md. Nor, Hasanan; Hainin, Mohd. Rosli (Lavoisier, 2008)
The objective of this research is to investigate the potential of using crumb rubber as a partial substitute for coarse sand in the production of concrete paving block (CPB). Laboratory trials were conducted to investigate the effect of crumb rubber particle size. A comparison was also made between CPB mixtures containing various percentages of crumb rubber to determine the optimum crumb rubber content and water-cement (w/c) ratio. Styrene-butadiene rubber (SBR) latex was added to the mixtures of crumb rubber CPB and mechanical properties were evaluated. A total of 276 CPB were fabricated and tested in laboratory to determine the density, skid resistance and the compressive strength. The design strength level ranging from 31 to 43 MPa was achieved using w/c ratios of 0.45 to 0.55. The test results indicated that there was a systematic reduction in the strength with the increase in rubber content. Scanning electron micrograph showed that inclusion of SBR latex into the matrix did not improve the mechanical properties of the CPB. Results also revealed that a w/c ratio of as high as 0.55 without any SBR latex at 15 % rubber content by total sand volume might be practically used to produce crumb rubber CPB which achieve the target compressive strength of 30 MPa.